1988
DOI: 10.1111/j.1365-2524.1988.hed2801026.x
|View full text |Cite
|
Sign up to set email alerts
|

Headache in Parkinson's Disease

Abstract: SYNOPSIS The presence of headache in Parkinson's disease has been recently reported in the literature. We studied 9cephalalgic parkinsonian patients compared to 8 parkinsonian patients taken as controls, both with clinical rating scalesand with EMG recordings of neck muscles. The presence of psychiatric disturbances was investigated by means ofseveral rating scales. Cephalalgic parkinsonian patients showed greater muscular activity and e higher degree ofanxiety and depression compared to the control group. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Other studies compared PD patients with and without headache and found that the 2 groups were similar in terms of PD symptoms. 7,8 To our knowledge, no other study has compared neck stiffness with the severity of headaches. We had expected to find this association, but we did not.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Other studies compared PD patients with and without headache and found that the 2 groups were similar in terms of PD symptoms. 7,8 To our knowledge, no other study has compared neck stiffness with the severity of headaches. We had expected to find this association, but we did not.…”
Section: Discussionmentioning
confidence: 99%
“…The sample size was based on previous studies about this subject. 6,7 All patients underwent computed tomography or magnetic resonance imaging of the head. Patients who had any cause of secondary headache detected in brain image were excluded.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It seemed that certain MG symptoms induce the development or worsening of headache, but there have been only a few case reports concerning headache in MG patients [1, 2]. On the other hand, some major neurological diseases, including Parkinson's disease [3, 4] and multiple sclerosis [5, 6], have been reported to be associated with headache. In this paper, to investigate the relationship between headache and MG, we examined whether each of the MG symptoms could be a cause of headache in MG patients.…”
Section: Introductionmentioning
confidence: 99%